Targeted modification of CmACO1 by CRISPR/Cas9 extends the shelf-life of Cucumis melo var. reticulatus melon - Nonaka, Satoko; Ito, Maki; Ezura, Hiroshi (Frontiers in Genome Editing, 2023)
in fruits. Extending fruit shelf-life reduces food loss, thereby contributing to food security. The enzyme 1-aminocyclopropane-1-carboxylic acid oxidase (ACO) is the final step of the ethylene production pathway, and its suppression via antisense technology has been demonstrated to extend the shelf-life of melon, apple, and papaya. The Melonet-DB (http://melonetdb.agbi.tsukuba.ac.jp/) showed that the melon genome had the five CmACOs and the gene CmACO1 predominantly expressed in harvested fruits. From this information, CmACO1 was expected to be a key gene for shelf-life in melons. We attempted to extend the shelf life in the Japanese luxury melon (Cucumis melo var. reticulatus) via modification of CmACO1 with the genome editing technology. Because the genome editing technology would not leave the exogenous genes in the final crop products, the crops via genome editing can be considered non-genetically modified crops. Compared to conventional breeding, such as mutation breeding, the breeding term would be expected to be quite short. From these points, Genome editing technology is an innovative technique for commercial application. In this study, CRISPR/Cas9 system, the genome editing technology, introduced the mutation on the CmACO1. The final product of this melon did not have any exogenous genes. The mutation was inherited for at least two generations. In the T2 generation, the fruit phenotypes 14 days after harvest were as follows: ethylene production was reduced to one-tenth that of the wild type, pericarp color remained green, higher fruit firmness. Early fermentation of the fresh fruit was observed in the wild-type fruit but not in the mutant. These results show that CmACO1 is a key gene for shelf-life in melons. Moreover, our result found that CmACO1 knockout via CRISPR/Cas9 extended the melon's shelf-life.